2013
DOI: 10.1016/j.bbamem.2013.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity to detergents of actin cytoskeleton from nerve endings

Abstract: Detergent-resistant membranes (DRM), an experimental model used to study lipid rafts, are typically extracted from cells by means of detergent treatment and subsequent ultracentrifugation in density gradients, Triton X-100 being the detergent of choice in most of the works. Since lipid rafts are membrane microdomains rich in cholesterol, depletion of this component causes solubilization of DRM with detergent. In previous works from our group, the lack of effect of cholesterol depletion on DRM solubilization wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Using cytochalasin D and immunoaffinity isolation of Mg 2+- stabilized DRMs, a recent study found that two archetypical GPI-anchored raft proteins, Thy-1 and PrP, are distributed to actin-dependent and independent DRMs, respectively, suggesting that a combination of methods interfering with the cytoskeleton is useful to differentiate specific lipid rafts (Chen et al, 2009). As standard operating procedure (SOP) it is recommended to use two methods to isolate DRMs (1% Triton X-100 at 4 °C and 1% Brij98 at 37 °C) or the detergent-free carbonate method should be combined with cholesterol depletion using pre-incubation with MβCD and F-actin depolymerization (latrunculin A or cytochalasin D), followed by immunoaffinity isolation of DRMs to determine lipid and protein composition in different lipid raft fractions (Cubi et al, 2013). Raft fractions should be tested for presence raft or raft-associated proteins such as flotillin (not GPI anchored), alkaline phosphatase (GPI-anchored), caveolin (not GPI anchored, specific for caveolae-type rafts), and transferrin receptor as a non-raft protein.…”
Section: Detection Preparation and Visualization Of Rafts And Theirmentioning
confidence: 99%
“…Using cytochalasin D and immunoaffinity isolation of Mg 2+- stabilized DRMs, a recent study found that two archetypical GPI-anchored raft proteins, Thy-1 and PrP, are distributed to actin-dependent and independent DRMs, respectively, suggesting that a combination of methods interfering with the cytoskeleton is useful to differentiate specific lipid rafts (Chen et al, 2009). As standard operating procedure (SOP) it is recommended to use two methods to isolate DRMs (1% Triton X-100 at 4 °C and 1% Brij98 at 37 °C) or the detergent-free carbonate method should be combined with cholesterol depletion using pre-incubation with MβCD and F-actin depolymerization (latrunculin A or cytochalasin D), followed by immunoaffinity isolation of DRMs to determine lipid and protein composition in different lipid raft fractions (Cubi et al, 2013). Raft fractions should be tested for presence raft or raft-associated proteins such as flotillin (not GPI anchored), alkaline phosphatase (GPI-anchored), caveolin (not GPI anchored, specific for caveolae-type rafts), and transferrin receptor as a non-raft protein.…”
Section: Detection Preparation and Visualization Of Rafts And Theirmentioning
confidence: 99%
“…The crude synaptosomal fractions (P2) were prepared from 4- to 6-week-old Sprague-Dawley rat brains, as described previously [ 45 ], with slight modifications. Animal samples were obtained according to a procedure approved by the Ethics Committee in Animal and Human Experimentation of the Universitat Autònoma de Barcelona (ref.…”
Section: Methodsmentioning
confidence: 99%
“…Detergent-resistant membranes (DRM) are an experimental model commonly used to study the so-called ‘membrane rafts’, which are cholesterol- and sphingolipid-rich dynamic membrane microdomains that incorporate specific proteins. DRM were extracted as described previously [ 45 ]. To obtain DRM, the medium was removed and the synaptosomal P2 fraction or MDCK cells were rinsed with cold PBS and homogenized at 4°C with sodium buffer containing 1% Triton X-100 by end-over-end mixing.…”
Section: Methodsmentioning
confidence: 99%
“…One of the common criticisms expressed regarding the purification temperature could be addressed when other less stringent detergents (e.g. Brij98) made it possible to purify DRMs at physiological temperature [20][21][22][23], although showing some notable differences between the methods and the choice of the detergent [24]. Another method emerged, consisting of aggregating these raft lipids with cholera toxin, which binds specifically to GM1 gangliosides, preferentially partitioning in DRMs, and considered as markers of the lipid raft [25].…”
Section: Pm Organization: From Historical Perspectives To Recent Advancesmentioning
confidence: 99%